Sovereign default and state-contingent debt - Martin Brooke; Rhys Mendes; Alex Pienkowski; Eric Santor (Bank of Canada, 2013)
The international community has a role to play in addressing this gap. In that regard, this paper is intended to stimulate debate on the problems in the current practices for sovereign debt restructuring and puts forward some proposals to improve the functioning of sovereign debt markets. The Bank of Canada and the Bank of England have collaborated on these issues in the past. For example, in 2001, Andy Haldane and Mark Kruger authored a joint paper on how to resolve sovereign debt crises in a more orderly and transparent manner. This current work builds on those ideas by exploring how state-contingent debt could further improve the system.
Keywords: F34; 330; International topics; International financial markets